Pengaruh Pengetahuan Keuangan, Sikap Keuangan Dan Kepribadian Terhadap Perilaku Manajemen Keuangan Pada Pelaku UMKM Di Kecamatan Air Putih Kabupaten Batubara - Tampubolon, Marjono; Rahmadani, Rahmadani (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2022)
The purpose of this research is to know how much influence of financial knowledge, the influence of financial attitude and the influence of personality towards financial management behavior on SMEs at Home Industrial Food on Air Putih Disctricts of Batubara Regency. This research is a quantitative study with a data-collection technique using a questionnaire. This research subject is the whole business of SMEs the Home-cooked culinary Industry, total of 45 SMEs subject. The sample retrieval technique used was non probability sampling through the saturated sampling method. The criteria established are at home culinary industries that make it about income a mounth, old business and number of employees. Primary data processing uses analysis technique statistical package for social science (SPSS) with multiple regression analysis methods and strip analysis. This research there was positive influence of financial knowledge towards financial management behavior, where as negative influence of financial attitude towards financial management behavior on SMEs temporary there was positive influence of personality towards financial management behavior on SMEs Home culinary Industry Air Putih district of Batubara Regency.